Mutant of Salmonella typhimurium LT2 deficient in DNA adenine methylation. - Ritchie, L J (1986)
A mutant of Salmonella typhimurium LT2 deficient in methylation of the adenine residues in the sequence 5'-GATC-3' was isolated. The mutation (dam-1) was linked to the cysG locus, and the properties of the mutant were similar to those of Escherichia coli dam mutants. Reversion of the hisC3076 frameshift marker by 9-aminoacridine was substantially enhanced by the dam-1 mutation, implying a direct role for adenine methylation in the prevention of frameshift mutation induction.